Bibliometric Analysis of Stablecoins - Muhammad Siraz; Adha Ita Lestary; Esa Desember Putri Pratama; Naufatti Aufa; Wahyu Akbar; Muhammad Riza Hafizi (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study presents a bibliometric analysis of the stablecoin literature indexed in Scopus from 2019 to 2026. Using the PRISMA protocol for literature selection and the Bibliometrix package in R for analysis, a total of 69 articles from 47 journals were examined. The results show an annual growth rate of 21.9%, with a peak of 19 articles published in 2024. The United States dominates research output, while the Journal of Risk and Financial Management is the most productive source. Lyons (2023) is the most cited document with 87 citations. Co-occurrence keyword mapping and thematic analysis identify blockchain, decentralized finance, and cryptocurrency as core research themes. At the same time, monetary policy, digital currencies, and central banks are emerging as frontier topics. Collaboration networks reveal fragmented clusters with limited cross-institutional integration. A significant research gap has been identified, including limited representation of developing countries, restricted regulatory analysis, and a lack of machine learning approaches. This research contributes to a structured knowledge map of stablecoins and provides a strategic agenda for future interdisciplinary research.